ダイ 7 ジ ナンキョク チイキ カンソクタイ 1965 1966 ナツタイ ホウコク - 村山, 雅美; ムラヤマ, マサヨシ; MURAYAMA, Masayoshi (国立極地研究所, 1966)
P(論文) (1) The basic plan of the 7th Japanese Antarctic Research Expedition was the reopening of the Syowa Station, the establishment of a permanent station and preparations for inland survey. The routine observations of the wintering team were to engage in the study of aurora, airglow, geomagnetism, ionosphere, natural earthquake observation and tidology at the station while high level scientific researches were to be made on auroral intensity, auroral spectrum, auroral radio noise emission, geomagnetic pulsation, ionospheric absorption, biology and thermal process in the upper atmosphere. Emphasis in the researches of the 7th Japanese Antarctic Research Expedition was to be placed on the study of upper atmospheric physics and biology in line with the International Quiet Sun Year (I Q S Y) and the International Biological Program (I B P), respectively The basic policy for inland survey was to be based on magnetic meridian which passes through the Syowa Station, and on geosciences, also glaciology and magnetism to be conducted between appropriate points on the magnetic meridian and the South Pole, were to be taken up as important subjects. Preparatory operations were to be made by the 7th wintering team with the target set on a South Pole traverse trip by the 10th expedition While testing the large sized snow car specially developed for such traverse, the wintering team was to conduct inland terrestrial magnetism and meteorological observations and also construct fuel depots for the team to accomplish the traverse. On the other hand, aboard the icebreaker FUJI, observations were conducted on upper stmosphere physics, oceanography, geochemistry and biology. (2) The icebreaker FUJI, which left Tokyo on November 20, 1965, entered the sea of ice floes off the Soviet Station Mirny on December 19 after touching at Fremantle, Australia. After proceeding westward, the FUJI arrived at the edge of close pack ice at a point 65°S, 45°E Compared with the conventional course via Gape Town, the time required to navigate the ...